(untitled) (Journal of Parents and Teachers, 2017)
Nowadays the widespread use of platforms and virtual resources significantly exposes our identity. This must be addressed by education in all its dimensions in order to facilitate its conceptualization and use. This way, parents and teachers as the linchpin of educational development must not ignore this aspect and have to respond pedagogically to these resources and tools.